Primary percutaneous intervention of the right coronary artery in a setting of anomalous origination of left coronary artery from the opposite sinus of Valsalva - Babić, Rade; Grujić, Goran; Kojić, Dejan; Kostić, Jelena; Trifunović, Zoran; Borović, Saša (Vojnosanitetski pregled, 2021)
Introduction. Coronary artery anomalies are infrequent but anticipated findings during percutaneous coronary interventions (PCI). Compared to consistent reporting in angiographic series, they seem to be underreported in interventional studies, and particularly in the setting of primary PCI, where their prompt recognition is of the utmost importance. Case report. We present a 50 years old male with inferior ST-elevation of myocardial infarction (STEMI) and right ventricular involvement with solitary ostium for all three coronary arteries in the right aortic sinus of Valsalva. The patient had an extremely rare variant of coronary artery origination belonging to the type A4b2c2 of Angelini’s classification. Correspondingly, it belongs to the left Anomalous origination of a Coronary Artery from the Opposite Sinus of Valsalva (ACAOS) class with the intraseptal course of left anterior descending artery. We managed successfully to implant a drug eluting stent in the proximal right coronary artery in a lengthy and stormy procedure, with the need for guiding catheter exchange, temporary pacing and dealing with no-reflow phenomenon. Conclusion. We summarize diagnostic hints for angiographic recognition of dominant variants of the left ACAOS and practical aspects of performing PCI in such patients. Also, we debate on the functional significance of coronary anomalies and its further implications from the prognostic and therapeutic aspects. We propose adoption of the novel classification of coronary anomalies of Angelini’s group in the routine clinical practice. Finally, we call for the inclusion of specific training in coronary artery anomalies into the interventional cardiology fellowship curriculum.
Keywords: percutaneous coronary intervention; coronary vessel anomalies; no-reflow phenomenon; st-elevation myocardial infarction